Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.05.06.442976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Palbociclib-mediated cell cycle arrest can occur in the absence of the CDK inhibitors p21 and p27

Abstract: The use of CDK4/6 inhibitors in the treatment of a wide range of cancers is an area of ongoing investigation. Despite their increasing clinical use, there is limited understanding of the determinants of sensitivity and resistance to these drugs. Recent data has cast doubt on how CDK4/6 inhibitors arrest proliferation, provoking renewed interest in the role(s) of CDK4/6 in driving cell proliferation. As the use of CDK4/6 inhibitors in cancer therapies becomes more prominent, an understanding of their effect on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Mechanistically, COPS5 mediated the degradation of P27 in a proteasome-dependent manner, thereby controlling its stability. P27 is a universal cyclin-dependent kinase (CDK) inhibitor that directly inhibits the enzymatic activity of the cyclin-CDK complex, resulting in cell cycle arrest in the G1 phase [20][21][22] . In our study, we also found that knocking down EEF1D can lead to cell G1/S phase arrest, and a decrease in CDK4, CDK6 and CyclinD1 proteins, which is closely related to EEF1D activation of the COPS5/P27 pathway, resulting in an increase in P27 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, COPS5 mediated the degradation of P27 in a proteasome-dependent manner, thereby controlling its stability. P27 is a universal cyclin-dependent kinase (CDK) inhibitor that directly inhibits the enzymatic activity of the cyclin-CDK complex, resulting in cell cycle arrest in the G1 phase [20][21][22] . In our study, we also found that knocking down EEF1D can lead to cell G1/S phase arrest, and a decrease in CDK4, CDK6 and CyclinD1 proteins, which is closely related to EEF1D activation of the COPS5/P27 pathway, resulting in an increase in P27 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This article has no additional data. The data are provided in the electronic supplementary material [70].…”
Section: Data Accessibilitymentioning
confidence: 99%